Integrating Artificial Intelligence into Economics Education: A Case Study on Educational Innovation in Türkiye - Garan, Özcan; Engin Balın, Billur (European Journal of Social Science Education and Research, 2026)
This study examines the role of artificial intelligence (AI) as a student support tool in higher education, specifically analyzing its benefits, limitations, and ethical challenges. The research explores students’ perceptions of AI, its impact on academic performance, and accessibility issues  Utilizing a qualitative case study approach, the study was conducted with students enrolled in the Environmental Economics course at Istanbul University, Faculty of Economics  Data were collected through focus group interviews to assess experiences with AI tools  Findings indicate that students view AI as a valuable asset that enhances productivity and facilitates learning by providing rapid access to information  However, concerns persist regarding the "robotic" quality of AI content, potential inaccuracies, and originality issues  Additionally, the study identifies digital inequality arising from paid AI features  By shifting the focus from the predominant medical applications of AI in Türkiye to the social sciences, this research fills a significant gap in the literature on AI integration in economics education.
Keywords: artificial intelligence, higher education, AI in higher education, student attitudes, digital literacy.